2008
DOI: 10.1007/s00535-008-2255-9
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density correlates with lymph node metastases and prognosis in hilar cholangiocarcinoma

Abstract: Neovascularization is associated with nodal spread as well as local recurrence and serves as an independent prognostic factor for survival after curative resection of hilar cholangiocarcinoma. Therefore, tumor-associated neovascularization seems to be critically involved in the progression of this tumor entity. In addition, neovascularization may represent a potential target in he development of new therapeutic approaches in hilar cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…Analysis of tumour-associated neovascularization indicates that angiogenesis occurs in CCA 189 and is critical for its progression [189][190][191][192] . iCCAs with high micro vessel density more frequently display advanced primary tumours and multiple tumour nodes 190 .…”
Section: Vascular Cellsmentioning
confidence: 99%
“…Analysis of tumour-associated neovascularization indicates that angiogenesis occurs in CCA 189 and is critical for its progression [189][190][191][192] . iCCAs with high micro vessel density more frequently display advanced primary tumours and multiple tumour nodes 190 .…”
Section: Vascular Cellsmentioning
confidence: 99%
“…Intrahepatic cholangiocarcinoma (IHCC) is well known to be one of the most malignant solid tumors in digestive organs [1][2][3][4][5]. We have already reported that lymph node metastases are seldom limited to the regional lymph nodes; most tumor recurrence occurs in the liver.…”
Section: Introductionmentioning
confidence: 98%
“…Microvessel synthesis has been considered to influence tumor metastasis and prognosis in various human cancers [19]. Interleukin 8 (IL-8) has received much attention with its role in microvessel synthesis in various tumors [20].…”
Section: Introductionmentioning
confidence: 99%